2011
DOI: 10.1021/ja2081444
|View full text |Cite
|
Sign up to set email alerts
|

Design of Chiral Bis-phosphoric Acid Catalyst Derived from (R)-3,3′-Di(2-hydroxy-3-arylphenyl)binaphthol: Catalytic Enantioselective Diels–Alder Reaction of α,β-Unsaturated Aldehydes with Amidodienes

Abstract: Chiral bis-phosphoric acid 1 was designed to identify a new class of structural features in chiral Brønsted acid catalysts. X-ray diffraction analysis revealed the single atropisomer 1, bearing S axial chirality at 3,3'-biaryl substituents on (R)-binaphthyl and intramolecular hydrogen bonding between the two phosphoric acid moieties. The newly designed bis-phosphoric acid 1 was evaluated in the Diels-Alder reaction of α,β-unsaturated aldehydes 4 with 1-N-acylamino-1,3-butadienes 3. After systematic variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…[31,36] The higher yield (79 %v s. 36 %) suggests that the presence of an additional phosphoric acid significantly increases theB rønsted-acidity, while the observed inverted stereoselectivity (99 %v s. À88 % ee for the (1S,6R)-product 18 a)p oints at an entirely different structure of the stereodetermining transition state. In the initial investigation,t he superior activity and selectivity of the symmetric triisopropylphenyl-substituted catalyst( R)-11 a wasd emonstrated in comparison to the TRIPm onophosphoric acid ((R)-10 b,s ee Scheme 8a nd Ta ble 1e ntries 1-2).…”
Section: Phosphoric Acids Combined With Additional Brønsted-acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,36] The higher yield (79 %v s. 36 %) suggests that the presence of an additional phosphoric acid significantly increases theB rønsted-acidity, while the observed inverted stereoselectivity (99 %v s. À88 % ee for the (1S,6R)-product 18 a)p oints at an entirely different structure of the stereodetermining transition state. In the initial investigation,t he superior activity and selectivity of the symmetric triisopropylphenyl-substituted catalyst( R)-11 a wasd emonstrated in comparison to the TRIPm onophosphoric acid ((R)-10 b,s ee Scheme 8a nd Ta ble 1e ntries 1-2).…”
Section: Phosphoric Acids Combined With Additional Brønsted-acidsmentioning
confidence: 99%
“…In the initial investigation,t he superior activity and selectivity of the symmetric triisopropylphenyl-substituted catalyst( R)-11 a wasd emonstrated in comparison to the TRIPm onophosphoric acid ((R)-10 b,s ee Scheme 8a nd Ta ble 1e ntries 1-2). [31,36] The higher yield (79 %v s. 36 %) suggests that the presence of an additional phosphoric acid significantly increases theB rønsted-acidity, while the observed inverted stereoselectivity (99 %v s. À88 % ee for the (1S,6R)-product 18 a)p oints at an entirely different structure of the stereodetermining transition state.…”
Section: Phosphoric Acids Combined With Additional Brønsted-acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent elegant progress has been disclosed with the aim of diversifying available chiral phosphoric acid scaffolds. [20] A novel catalyst architecture able to effectively emulate TRIP, while at the same time providing new opportunities for catalyst modification is an exciting proposition. Accordingly, we found that PhDAP catalyzes the formation of cyclic aminals with selectivities comparable to those reported using BINOL-derived phosphoric acids [Eq.…”
Section: Entry Substratementioning
confidence: 99%
“…[3] The independent research of Akiyama et al as well as Uraguchi and Terada made 1,1'-bi-2-naphthol (BINOL) phosphoric acids fashionable as asymmetric catalysis in 2004. [4] Since then, other novel BINOL-based organic acids have been developed, such as N-triflyl phosphoramides, [5] dicarboxylic acids, [6] disulfonic acids, [7] chiral sulfonimides, [8] and chiral bis-phosphoric acids, [9] with the intention of expanding the scope of substrates and finding new reaction patterns (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%